1.a)a. (x-1)(x-2)=x^2-2x-x+2=x^2-3x+2
b. (x-3)(x+6)=x²+6x-3x-18=x²+3x+18
c. (x+4)(x+5)=x²+5x+4x+20=x²+9x+20
d. (2x+7)(x-2)=2x^2-4x+7x-14=2x²+3x+14
e. (1-2x)(3x+5)=3x+5-6x²-10x=6x²-7x+5
f. (2x+3)(5x-4)=10x²-8x+15x-12=10x²+7x-12
g. (2x+3b)(3a-b)=6ax-2bx+9ab-3b²
h. (4x+3y)(4x-3y)=16x²-9y²
2.a)a. -2xy(x+3y) + 4x(xy-y²)=-2x²y-6xy²+4x²y-4xy²=6x²y-10xy²
b. 3x(2x-1) + (x+2)(x-5)=6x²-3x+x²-5x+2x-10=7x²-6x-10
c. (x+4)(x-3) - (x-1)(x+6)=x²-3x+4x-12-x²-6x+x+6= -4x-6
d. 5x(x-4) - (x-3)(5x+2)=5x²-20x-5x²-2x+15x+6=-7x+6
e. (7x-1)(x-3) - 5(x+2)(x+4)=7x²-21x-x+3-5(x²+4x+2x+8)=7x²-20x+3-5x²-20x-10x-40=2x²-50x-37